The Riverine Archive: Nausea and information loss on the neoliberal ship of fools. (August 2022) - Antonopoulou, Alexandra; Dare, Eleanor
Within academia, as in other corporatized environments, there are irreconcilable tensions embedded in the managerial data imaginary, in contrast to the messy reality of lived experience and increasingly precarious working conditions for those at the coalface of Higher Education. Combined with student debt and escalating surveillance via so-called 'artificially intelligent' transactional data analysis, fantasies of control and domination converge on platitudes about Big Data and computational information, often presented as unambiguously neutral via idealized visualizations and 'dashboards' such as those commonly provided by Tableau and Google. As a structure, the digital archive is no different, open to fantasies of secure representation but, in fact, always unstable, subject to the materiality and flux of electronic, symbolic and social processes. As academics exposed to intensified metricization within increasingly data driven institutions, how can we counter the reduction of our qualitative research and experience to dashboards and scores? Drawing upon the work of Fleming's Dark Academia: How Universities Die (2021), Poster's The Mode of Information (1990), Cascella's En Abime: Listening, Reading, Writing: An Archival Fiction (2012) and Bayne et al.'s The Manifesto for Teaching Online (2020) among others, and focusing on work developed by the authors from 2008 onwards, they discuss their contingent, often nauseating virtual reality information repository, the Riverine Archive, developed to hold and withhold information about their writing and art within the ugly hulk of what they define as a 'neoliberal ship of fools'. The work seeks to offer a counter to prevailing platitudes and fantasies about the neutrality and realism of data to directly represent a stable, singular reality. The authors concur that information is not beautiful, but rather a fallacy of stability, servicing a rapacious, anti-academic neoliberal ideology that needs to be brought to the surface and subjected to honest discourse, away from hype and managerial wishful thinking. Truth and beauty cannot be framed as stable, monolithic or universal; to do so is to replicate a colonial projection of knowledge, a mono-logic, centring all truth upon the Global North.